2013
DOI: 10.1002/pds.3484
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic medication use in adolescents with intellectual disability living in the community

Abstract: Adolescents with intellectual disability use a wide range of psychotropic medications. Being male and having major behaviour problems are associated with the use of psychotropic medications. Research examining the rationale for psychotropic prescribing in this population is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 56 publications
(133 reference statements)
0
15
0
Order By: Relevance
“…The system for coding medication use (WHO ; WHOCC – ATC/DDD ) has been used in other studies of medication use in individuals with ID (Scheifes et al ; Doan et al ). The ATC system groups medications into 14 categories according to the organs or system on which they act or their chemical, pharmacological or therapeutic characteristics (Doan et al ). Medication was independently coded by an Intellectual Disability Nurse, with research experience, who was an independent and supplementary prescriber (v300 Qualification).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The system for coding medication use (WHO ; WHOCC – ATC/DDD ) has been used in other studies of medication use in individuals with ID (Scheifes et al ; Doan et al ). The ATC system groups medications into 14 categories according to the organs or system on which they act or their chemical, pharmacological or therapeutic characteristics (Doan et al ). Medication was independently coded by an Intellectual Disability Nurse, with research experience, who was an independent and supplementary prescriber (v300 Qualification).…”
Section: Methodsmentioning
confidence: 99%
“…The system for coding medication use (WHO 2014; WHOCC -ATC/DDD 2014) has been used in other studies of medication use in individuals with ID (Scheifes et al 2013;Doan et al 2014).…”
Section: Medication Datamentioning
confidence: 99%
See 1 more Smart Citation
“…These diagnoses and their subsequent coding were checked by a general practitioner with extensive experience in intellectual disability medicine. 17 Symptoms and conditions were coded according to the International Statistical Classification of Disease and Related Health Conditions (ICD-10) 14 and are reported by chapter.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of a high burden of diseases [7][8][9], polypharmacy, whose definition may vary across studies but most frequently denotes the use of 5 or more medications [10], is frequent among this population [11][12][13][14] and nonadherence can be an issue [15]. A study in primary care in the Netherlands revealed that 75% of people with DDs received medication compared with 59% individuals in the matched control group [16].…”
Section: Introduction Backgroundmentioning
confidence: 99%